Expositive written composition from the psycholinguistic model of Flower and Hayes: Strategies for its enhancing (Quaestiones Disputatae: temas en debate, 2021)
This paper shows the results of a research whose goal deals with improving the expositive texts writing process from the psycholinguistic model of Flower and Hayes, of students belonging to the first semester of the undergraduate program in Physicalical Culture, Recreation and Sports in Universidad Santo Tomás, Tunja. The research was framed in qualitative research perspective, spcifically action research. This study was carried out by means of four stages: diagnosis, action plan developing concerning to the design of didactic units, the implementation of the pedagogical proposal and the evaluation of the implemented proposal. The results indicate the achievements in the appropriation of the phases of the psycholinguistic model and the development of cognitive and metacognitive strategies as well as the improvementof the textual competencies required for the students when writing.
Keywords: Written composition; psycholinguistic model of Flower and Hayes; cognitive and metacognitive strategies; expositive text